2022
DOI: 10.1002/jsid.1112
|View full text |Cite
|
Sign up to set email alerts
|

Light‐field head‐mounted displays reduce the visual effort: A user study

Abstract: Head‐mounted displays (HMDs) allow the visualization of virtual content and the change of view perspectives in a virtual reality (VR). Besides entertainment purposes, such displays also find application in augmented reality, VR training, or tele‐robotic systems. The quality of visual feedback plays a key role for the interaction performance in such setups. In the last years, high‐end computers and displays led to the reduction of simulator sickness regarding nausea symptoms, while new visualization technologie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
1
3
1
Order By: Relevance
“…Obviously, the subjects tried to use the additional information of the light-field display (potentially increased confidence) and to correct the position accordingly, even if they could not achieve a more accurate result compared to the condition without light-field. Contrary to the prior study 9 (where the depth map was perfect and 3D instead of 2.5D), no evidence was found that light-field technology directly reduces the visual strain of the human operator and no effects in the SSQ and VSQ queries were found. Yet, the overall workload ratings indicated lower values when light-field was available compared to the condition without.…”
Section: H1contrasting
confidence: 85%
See 4 more Smart Citations
“…Obviously, the subjects tried to use the additional information of the light-field display (potentially increased confidence) and to correct the position accordingly, even if they could not achieve a more accurate result compared to the condition without light-field. Contrary to the prior study 9 (where the depth map was perfect and 3D instead of 2.5D), no evidence was found that light-field technology directly reduces the visual strain of the human operator and no effects in the SSQ and VSQ queries were found. Yet, the overall workload ratings indicated lower values when light-field was available compared to the condition without.…”
Section: H1contrasting
confidence: 85%
“…In literature, for instance, holographic displays 11 and such based on microlens arrays, multiple depth planes, 12,13 or varifocal elements (e.g., focus‐tunable lenses 14,15 or deformable membrane mirrors 16 ) were proposed to display different depth areas. The light‐field head‐mounted display of this work (Creal Zorya 17 ) was already applied in Panzirsch et al 9 . This work confirmed for the first time that light‐field HMDs can reduce the visual effort for the user in VR applications with perfect visual information.…”
Section: Introductionsupporting
confidence: 74%
See 3 more Smart Citations